Further development and feasibility randomised controlled trial of a digital programme for adolescent depression, MoodHwb: study protocol - Marcela Gavigan; Sharon Anne Simpson; Jonathan I Bisson; Rebecca Playle; Frances Rice; Vince Poile; Anna Gray; Elaine Hindle; Sally Merry; Rachel McNamara; Rhys Williams-Thomas; Elizabeth Randell; et al. (BMJ Open, 2023)
Introduction A digital programme, MoodHwb, was codesigned with young people experiencing or at high risk of depression, parents/carers and professionals, to provide support for young people with their mood and well-being. A preliminary evaluation study provided support for the programme theory and found that MoodHwb was acceptable to use. This study aims to refine the programme based on user feedback, and to assess the acceptability and feasibility of the updated version and study methods.Methods and analysis Initially, this study will refine MoodHwb with the involvement of young people, including in a pretrial acceptability phase. This will be followed by a multicentre feasibility randomised controlled trial comparing MoodHwb plus usual care with a digital information pack plus usual care. Up to 120 young people aged 13–19 years with symptoms of depression and their parents/carers will be recruited through schools, mental health services, youth services, charities and voluntary self-referral in Wales and Scotland. The primary outcomes are the feasibility and acceptability of the MoodHwb programme (including usage, design and content) and of trial methods (including recruitment and retention rates), assessed 2 months postrandomisation. Secondary outcomes include potential impact on domains including depression knowledge and stigma, help-seeking, well-being and depression and anxiety symptoms measured at 2 months postrandomisation.Ethics and dissemination The pretrial acceptability phase was approved by the Cardiff University School of Medicine Research Ethics Committee (REC) and the University of Glasgow College of Medicine, Veterinary and Life Sciences REC. The trial was approved by Wales NHS REC 3 (21/WA/0205), the Health Research Authority(HRA), Health and Care Research Wales (HCRW), university health board Research and Development (R&D) departments in Wales, and schools in Wales and Scotland. Findings will be disseminated in peer-reviewed open-access journals, at conferences and meetings, and online to academic, clinical, and educational audiences and the wider public.Trial registration number ISRCTN12437531.